Marketers and Avertisers and the Concept Called “Aggressive Marketing Tendency (ATM)” - Bethel Chidiebere Uzoagba; Micheal A. Nza-Ayang; Olimma Benedette Ngozi (International Journal of Global Sustainable Research, 2024)
In recent times, advertisers and marketers have realised that constant exposure to outdoor advertisement increases the tendency of brand familiarity as a result, propels patronage. Okoro (1998:77) supports this when he said that outdoor advertising makes product highly visible to the consumers, thereby enhancing recall-readiness of brand names. This is because the advert message is viewed so many times a day by same people. As a result helps to fix the brand name on the consumers’ mind